S25 Arterial Stiffness and Airway Infection and Inflammation During COPD Exacerbations. (19th November 2012) - Patel, ARC; Kowlessar, BS; Sapsford, R; George, SN; Garcha, DS; Donaldson, GC; Mackay, AJ; Singh, R; Wedzicha, JA; Hurst, JR
Abstract : Introduction: Cardiovascular risk is elevated following COPD exacerbations requiring systemic therapy (Donaldson et al, Chest 2010:137; 1091–7). We have recently shown that a potential mechanism is increased arterial stiffness during COPD exacerbations compared to the stable state (Patel et al, AJRCCM 2012:185; A5853). We hypothesised that arterial stiffness may be mediated by airway infection and inflammation during COPD exacerbations. Methods: We used aortic pulse wave velocity (aPWV) as a non-invasive validated measure of arterial stiffness using Vicorder apparatus (Skidmore Medical, UK) in outpatients from the London COPD cohort when they presented within seven days of exacerbation symptom onset and prior to any systemic therapy. These events were defined using our usual symptomatic criteria (Seemungal et al, AJRCCM 1998:157; 1418–22). We collected spontaneous sputum at the same clinic visit to identify typical bacterial ( S pneumoniae, H influenzae and M catarrhalis ) and rhinovirus infection using PCR. We also measured IL-6 and IL-8 in sputum supernatant using commercial ELISA kits (R&D Systems, USA). Results: 32 exacerbating COPD patients produced a spontaneous sputum sample during the same clinic visit as an aPWV measurement. Their stable clinical characteristics were: 69% male; 25% current smokers; median (IQR) 39 (21.74) pack year smoking history; mean±SD age 72.4±8.1 years; FEV1 1.18±0.41L and 46.8±18.0%predicted; FEV1/FVC ratio 0.44±0.15 and BMI 25.4±3.8 kg/m2. Arterial stiffness was higher in patients with airway infection at exacerbation presentation (mean ±SD aPWV 12.3±2.3 (n=19) vs 10.8±1.8 (n=13) m/s, p=0.030) (Figure 1A ). Arterial stiffness was strongly correlated with sputum IL-6 at exacerbation (n=32, rho=0.495, p=0.003) (Figure 1B ) but not IL-8 (n=31, rho=0.100, p=0.591). Conclusions: Arterial stiffness is related to airway infection and inflammation during COPD exacerbations. Interventions to prevent and reduce airway infection and inflammation may lower cardiovascular risk during COPD exacerbations.